(untitled) (International Journal of Built Environment and Sustainability, 2017)
The Northern Region of Nigeria, which is located south of Africa biggest desert - the Sahara, is highly vulnerable to adverse impacts of climate change for some reasons. This paper attempts to review the variance between urban greenery, urban development and the quest for environmental sustainability. A critical review of relevant materials related to the study was carried out. The quantitative nature of the study was backed empirically. Findings from the study reveal that physical development plans for some urban areas have been very ad-hoc and loosely defined. Allocation of open green spaces is not in harmony with the urban population and it mostly characterized by a low percentage. Abuja master plan, for instance, has the highest allocation of 32.87%, while allocation in other master plans fall below 30% with Suleja master plan counts 2.5% only. Outdated master plan and the lack of will power from urban authority in plan implementation has often resulted in the distortion, encroachment, and conversion of green areas to other land uses. Increase carbon emission and pollution especially from the transport sector has been marked by a decline in greenery. Therefore, reducing the sequestration capacity of the urban area, weak urban planning and harsh climatic condition could be regarded as critical challenges. This study suggests the strict adherent to sustainable urban planning that integrates physical development and environmental consideration to enhance greenery. The study also recommends the placement of urban greenery on the same platform with the urban grey infrastructure by urban stakeholders.